All four dengue virus serotypes co-circulate in concurrent dengue infections in a single dengue session in Chittagong, Bangladesh - Roy, Moushumi Ghosh; Uddin, Kutub; Islam, Din; Singh, Anjuvan; Islam, Mohammad Monirul (Bioresearch Communications, 2021)
Purposes: Dengue fever, a mosquito-borne viral disease, is a global public health burden affecting millions of people each year and over 40% of world populations are at risk of dengue. Therefore, prompt and accurate dengue diagnosis is inevitable for disease surveillance and for aiding disease management. In this study we report dengue virus (DENV) seroprevalence in Chittagong, Bangladesh along with clinical manifestation of dengue infections. Methods: All samples included in this study were selected based on dengue NS1-based diagnosis, clinical sign and symptoms were judged by expert clinical physicians and infecting DENV serotyping was done by RT-PCR. The blood cells (Platelet, Haematocrit, WBC etc) were analyzed using Haematology cell counter. Results: First, among the 112 DENV infected serum samples tested by RT-PCR, 42 were DENV positive where 76% samples had single DENV serotype infection and 24% were concurrently infected with two or more DENV serotypes, indicating that all four DENVs were present in a single dengue session in Chittagong, Bangladesh. Then, DENV4 was the most prevailed serotype, followed by DENV2, DENV1 and DENV3 in single DENV serotype infections. However, in almost 90% cases of concurrent multiple DENV infections DENV1 serotype was present. A detail analysis of clinical data clearly indicated that DENV1 and DENV2 resulted very similar patterns of clinical symptoms which were quite different from those caused by DENV3 and DENV4. For example, ache and pain were absent in DENV3 infection and diarrhea was absent in DENV4 infections. Furthermore, DENV3, both in single and concurrent multiple DENV infections, might increase dengue disease severity as observed highly reduced platelet counts along with increased WBC in patients infected with DENV3 serotype. Conclusion: All four DENV serotypes, both as single and concurrent multiple DENV infections, were present in single dengue session in Bangladesh. Despite having very similar sequences and structures all four DENVs might produce different disease spectra, ranging from classical dengue fever to dengue hemorrhagic fever. Concurrent multiple DENV infections could contribute increased dengue disease severity in dengue outbreaks in Bangladesh. Bioresearch Commu. 8(1): 1042-1048, 2022 (January)